Pelatihan Penyusunan Laporan dan Pelaporan Pajak untuk Koperasi Kabupaten Pindrang - Dahniyar Daud; Hisnol Djamali; Haliah; Gunawan; Yudi Akhmad Sadeli; Abdul Rival; Muhammad Alif (LP2M IAIN Sultan Amai Gorontalo, 2022)
This training aims to enhance understanding of the processes for recording, preparing, and reporting taxes for Pinrang Regency cooperatives. The participants in this program were the managers and supervisors of each cooperative registered in Pinrang Regency, with 25 participants representing each of the 72 cooperatives in Pinrang Regency. This research method employed a participatory strategy in which subject-matter experts present material in lectures, followed by direct discussions and training on developing joint tax returns. In addition to completing a questionnaire, participants in the BUMDes financial training also employed this strategy. The outcomes of this training indicated that the socialization of tax preparation procedures for cooperatives enhanced managers' knowledge of tax preparation and reporting strategies.